The Role of Sports Activities in Enhancing English Language Learning Motivation: Analysing the Impact - Dandan Tian; Haibo Xue (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study investigates the influence of sports activities on English Language Learning Motivation (ELLM), with a particular focus on how interaction and cooperation within these activities impact students in multilingual environments. Data were collected through surveys administered to 150 students who engaged in sports as part of their ELLM program. Leveraging theories of the interaction hypothesis and cooperative learning, the research examines how real-life communication scenarios in sports—such as teamwork, game instructions, and peer interactions—offer authentic opportunities for language use. These experiences are shown to significantly enhance students' motivation to learn English by increasing language usage frequency and boosting confidence. The study also explores the distinct challenges and opportunities presented by multilingual contexts, demonstrating how sports activities can act as a dynamic tool to mitigate language anxiety and facilitate language acquisition. The results reveal moderate to strong positive correlations between teamwork (r = 0.65), game instructions (r = 0.70), and peer interactions (r = 0.75) with ELLM. ANOVA results indicate significant variations in motivation related to participation in teamwork (F (2, 96) = 12.45, p < 0.01), game instructions (F (2, 97) = 9.32, p = 0.0002), and peer interactions (F (2, 97) = 14.67, p < 0.0001). However, post-hoc analysis suggests that while peer interactions positively affect motivation, the effects of teamwork, game instructions, and peer interactions on motivation do not differ statistically. This paper provides practical insights into integrating sports into language education, advocating for a more engaging and effective learning environment through a blend of theoretical analysis and empirical research, including surveys, interviews, and classroom observations.